Issues at the Rural-Urban Fringe: Hillsborough County Agriculture Stewardship Program - Rodney L. Clouser; Stephen Gran (EDIS, 2007)
FE701, an 8-page fact sheet by Rodney L. Clouser and Stephen Gran, describes a stewardship program developed to prevent premature conversion of agricultural land in this rapidly growing county surrounding Tampa Bay. Includes references. Published by the UF Department of Food and Resource Economics, November 2007.